The Age of Phillis - Jeffers, Honoree Fanonne, 1967- (Book collections on Project MUSE., 2020)
"In 1773, a young, African American woman named Phillis Wheatley published a book of poetry that challenged Western prejudices about African and female intellectual capabilities. Based on fifteen years of archival research, The Age of Phillis, by award-winning writer Honoree Fanonne Jeffers, imagines the life and times of Wheatley: her childhood in the Gambia, West Africa, her life with her white American owners, her friendship with Obour Tanner, and her marriage to the enigmatic John Peters. Woven throughout are poems about Wheatley's "age"--The era that encompassed political, philosophical, and religious upheaval, as well as the transatlantic slave trade. For the first time in verse, Wheatley's relationship to black people and their individual "mercies" is foregrounded, and here we see her as not simply a racial or literary symbol, but a human being who lived and loved while making her indelible mark on history."--